THE ANALYSIS OF THE TIMELINESS OF FINANCIAL STATEMENTS (AN EMPIRICAL STUDY ON CONSUMER GOODS SUBSECTOR LISTED ON IDX 2018-2021) - Janice Lovell; Karina Harjanto (Universitas Multimedia Nusantara, 2023)
Abstract- The timeliness of financial statements is regarded as one of the qualitative attributes of financial statements, denoting the availability of information for decision-making purposes prior to its diminished capacity to impact decisions. The objective of this study is to gather empirical data on the impact of profitability (ROA), leverage (DER), liquidity (CR), and institutional ownership on the promptness of financial statement reporting. The focus of this study encompasses consumer products firms that are publicly traded on IDX within the time frame of 2018 to 2021. The present study employed secondary data and employed a purposive sampling technique to select and analyze samples, utilizing logistic regression as the primary analytical tool, resulting in research sample of 25 companies. The findings indicate that there is no significant impact of profitability and liquidity on the timeliness of financial statement reporting. However, the study does find a significant positive relationship between leverage and the timeliness of financial statement reporting. Additionally, institutional ownership is found to have a positive and significant effect on the timeliness of financial statement reporting. The simultaneous impact of liquidity, profitability, leverage, and institutional ownership on the timeliness of financial statement reporting is found to be considerable. Keywords: Institutional Ownership; Leverage; Liquidity; Profitability; Timeliness of Financial Statement Reporting